Creating change agents for interprofessional education and practice: a leadership programme for academic staff and health practitioners - Brewer, Margo; Flavell, Helen; Trede, F.; Smith, M. (2017)
Universities face increasing pressure not only to embed interprofessional education within health education curricula but also to prepare graduates as catalysts of change for interprofessional, team-based approaches to health care delivery. Currently, few leadership programmes exist that support the expansion of interprofessional education. This paper describes the development, implementation and evaluation of a leadership programme aimed to build faculty and health practitioners’ capacity to become change agents for interprofessional education and practice. The programme was delivered by two Australian universities, each in partnership with a local health care provider. A mixed method approach was adopted to measure participants’ pre- and post- knowledge, reactions to the programme, planned and reported behavioural changes, and organizational outcomes. The programme was positively evaluated and reported to increase participants’ understanding of interprofessional education and practice. Follow up with participants suggested the programme had facilitated the implementation of interprofessional education and practice in both academic and practice contexts.